Potato plant growth and macronutrient uptake as affected by soil tillage and irrigation systems - Nunes, Julio Cezar Silveira; Fontes, Paulo Cezar Rezende; Araújo, Eduardo Fontes; Sediyama, Carlos (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this study was to evaluate potato plant growth and macronutrient uptake, as affected by soil tillage methods, in sprinkle and drip irrigated experiments. Eight treatments were set: T1, no tillage, except for furrowing before planting; T2, one subsoiling (SS); T3, twice rotary hoeing (RH); T4, one disc plowing (DP) + twice disc harrow leveling (DL); T5, 1DP + 2DL + 1RH; T6, 1DP + 2DL + 2RH; T7, 1SS + T6; T8, one moldboard plowing (MP) + 2DL. Treatments were arranged in a randomized block design with four replications. In both irrigation systems, plants presented higher emergence velocity index (EVI), when the soil was not tillaged, and the EVI was inversely related to the maximum tuber dry mass production. In both experiments, a functional direct relationship was found between the leaf area index and maximum tuber dry mass yield. The growth of plant organs (tuber, leaf, stem and root) and the macronutrient (N, P, K, Ca and Mg) contents in potato plant responded positively to a deeper soil revolving caused by plowing, especially with moldboard plow.
Keywords: Solanum tuberosum; moldboard plow; minimum tillage